An innate immune signature induced by AS01- or AS03-adjuvanted vaccines predicts the antibody response magnitude and quality consistently over time - Tasdighian, Setareh; Bechtold, Viviane; Essaghir, Ahmed; Saeys, Yvan; Burny, Wivine (Frontiers in Immunology, 2024)
Background: Antibody-mediated protection can depend on mechanisms varying from neutralization to Fcdependent innate immune-cell recruitment. Adjuvanted vaccine development relies on a holistic understanding of how adjuvants modulate the quantity/titer and quality of the antibody response.A Phase 2 trial (ClinicalTrials.gov: NCT00805389) evaluated hepatitis B vaccines formulated with licensed adjuvants (AS01 B , AS01 E , AS03, AS04 or Alum) in antigen-naïve adults. The trial investigated the role of adjuvants in shaping antibody-effector functions, and identified an innate transcriptional response shared by AS01 B , AS01 E and AS03. We integrated previously reported data on the innate response (gene expression, cytokine/C-reactive protein levels) and on quantitative/qualitative features of the mature antibody response (Fc-related parameters, immunoglobulin titers, avidity). Associations between the innate and humoral parameters were explored using systems vaccinology and a machine-learning framework.Results: A dichotomy in responses between AS01/AS03 and AS04/Alum (with the former two contributing most to the association with the humoral response) was observed across all timepoints of this longitudinal study. The consistent patterns over time suggested a similarity in the impacts of the two-dose immunization regimen, year-long interval, and non-adjuvanted antigenic challenge given one year later. An innate signature characterized by interferon pathway-related gene expression and secreted interferon-γ-induced protein 10 and C-reactive protein, which was shared by AS01 and AS03, consistently predicted both the qualitative antibody response features and the titers. The signature also predicted from the antibody response quality, the group of adjuvants from which the administered vaccine was derived.An innate signature induced by AS01-or AS03-adjuvanted vaccines predicts the antibody response magnitude and quality consistently over time.